Circadian control of hepatitis B virus replication - Xiaodong Zhuang (Nature Portfolio, 2021)
The circadian factors BMAL1/CLOCK and REV-ERB are master regulators of the human liver transcriptome but their role in hepatitis B virus infection is largely unknown. Here, Zhuang et al. show that REV-ERB regulates hepatitis B virus entry and BMAL1 directly binds HBV DNA and activates viral genome transcription.